Pengembangan Aplikasi Fishio Sebagai Alternatif Media Penjualan Hasil Budidaya Perikanan - Arif Rahman; Adam Hendra Brata; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Fishio is a marketplace that connects fish farmers and consumers. Based on the Indonesian KKP data in 2018 there was an increase in fisheries production reaching 17.22 million tons at the end of 2017. However, this potential was not in line with the conditions of fish pond farmers. Cultivators often complain about sales that don't sell because of difficult marketing. Therefore the author took the initiative to create media marketing through the application. The application that facilitates the marketing process will help farmers and consumers order and find their needs. This aims to make it easier for fisheries farmers to market their products so far and make it easier for consumers to order pond fisheries products. Application development uses the prototyping method as a software development method because the application is intended for many users so that in the future there can be an iteration in its development. Using the Android and Firebase platforms as service providers is expected to be able to solve existing problems. This application gets a value of 67.5 from a scale of 100 for seller applications and a value of 75 from a scale of 100 for buyer applications.